English teachers’ methods in teaching reading comprehension of procedure text - Yusmalinda, Akidatul; Astuti, Puji (ELT Forum: Journal of English Language Teaching, 2020)
This study focuses on English teachers’ methods in teaching reading comprehension of procedure text. The main purpose of this study is to describe the methods used by English teachers and reveal the strengths and weaknesses of those methods used for teaching reading comprehension of procedure texts. The research was a qualitative case study. The participants of this research were two English teachers at one of junior high schools in Semarang in the academic year of 2019/2020. In collecting data, several data collection instruments were used, including: interview, observation guideline and document analysis checklist. The findings showed that English teachers planned the teaching materials and strategies in advance. They also used various methods in teaching reading of procedure text. Both teachers almost used the same methods which were audio-visual method, scaffolding, grammar-translation method, and project-based learning. The difference was in the step of the strategy implementation. In addition, the findings showed that the most appropriate method in teaching reading comprehension was grammar-translation method since it helped students comprehend the procedure text. There were several students who still had a hard time following the lessons. Teachers are supposed to make sure that all students have understood the whole text or not and they should observe the students’ situation and needs so that the teaching and learning is contextual.